Self-Fulfilling History: How Narrative Shapes Preservation of the Online World. - Weber, Marc (Information & Culture, 2016)
New topics in the history of technology develop through stages. For the history of the online world, different stages have been marked by different dominant interpretations, moving from technical and teleological narratives about just a few favored systems and individuals to a more eclectic mix. Narratives are also influenced by still-living pioneers. But these changing stories are not just interesting for the historiography of cyberspace. They directly affect what source material gets valued and thus preserved, an effect hugely amplified by the fragility of digital media. Early biases can become self-fulfilling by erasing the source materials that could support competing points of view. This article details practices that have developed in response to such challenges at collecting institutions, using the Computer History Museum as a case study in the hope that it may prove useful to others.